Syntax. Issue 2 (10th December 2014) - Adger, David
Abstract : Syntax is the cognitive capacity of human beings that allows us to connect linguistic meaning with linguistic form. The study of syntax is a huge field that has generated a great deal of empirical and theoretical work over the decades. This article outlines why understanding our syntactic capacity is important to cognitive science in general and why the data of syntactic research is to be taken seriously. It then provides an overview of a number of broad findings about the character of the syntax of human language, including evidence for abstract constituent structure, core properties of constituents, the importance of functional categories, the link between syntactic structure and meaning, and the range of types of syntactic dependencies, including dependencies of form, dependencies of position, and dependencies that create new meanings. WIREs Cogn Sci 2015, 6:131–147. doi: 10.1002/wcs.1332 This article is categorized under: Linguistics > Language in Mind and Brain Linguistics > Linguistic Theory Psychology > Language